Early Management and Fluid Resuscitation - Kaya Yorgancı (Galenos Yayinevi, 2011)
Initial management of severely burned patient is similar with a trauma victim. Determination of airway patency, evaluation of respiration and circulation, early recognition of concomitant trauma has vital importance in burn patients. In the early phase, mortality mainly depends on missed or un-treated severe injuries or pathologies, but not burn injury itself.In patients that have TBSA greater than 15 %, fluid resuscitation should be started. In the first 24 hours, crystalloid solutions should be preferred. .Several formulas can guide fluid resuscitation; however the amount of fluid that is given to the patient should be individualized according to the patient's need. (Journal of the Turkish Society Intensive Care 2011; 9 Suppl: 7-10)